Morphometric tools to solve species complexes: The case of Rhagovelia angustipes (Hemiptera: Veliidae) - Galindo-Malagón, Ximena Alejandra; Morales, Irina; Ospina-Garcés, Sandra M. (Arthropod structure & development, 2022)
The riffle bugs of the Rhagovelia angustipes complex have presented problems in taxonomy due to high intra-specific variability. Here we identified variation in the complex with morphometric techniques. We analyzed variation of the characters and performed a phylogenetic analysis of a combined matrix of linear measurements, geometric configurations, and discrete characters. We found that characters such as head length, metanotum length, femur width, and the evaluated shape of four characters (head, abdomen, fore tibia, hind femur) were important for the delimitation of species. In particular, we identified the metanotum length as a character that had not been previously considered in the taxonomy of the complex. The phylogenetic reconstruction allowed us to recover some relationships established for the taxonomy of the complex for the salina group, except for the species R. colombiana that was closer to R. calceola and R. calopa. This may be due to a similar natural history, since they share areas of distribution, while the R. bisignata and R. hambletoni groups could not be recovered, showing their low morphological support. In general, the geometric morphometric characters showed high levels of homology, with the head and the anterior tibia being the ones that had the best performance in the tree. Finally, the use of morphometric tools proved to be a powerful input for the taxonomic resolution of species complexes that have problems in their delimitation. •Linear and geometric morphometrics identify characters for species discrimination.•Variance in shape characters solves species inconsistencies in the Rhagovelia angustipes complex.•Phylogenetic reconstruction of characters suggests new relationships in the taxonomy of the complex.